Composite current collector and preparation method thereof, electrode and secondary battery
By forming a modified layer on the surface of the polymer base membrane of the composite album, the problem of insufficient adhesion between the polymer polymer base film and the metal layer is solved, and the structural stability and battery performance of the composite collective fluid are improved.
Patent Information
- Application Number
- CN202211705240.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-29
AI Technical Summary
The bonding force between the polymer base film and the metal layer in the existing composite liquid is weak, resulting in poor structural stability and affecting its normal use.
The modifier layer is formed on the surface of the polymer base membrane. The modifier layer is composed of a polymer formed by the inner formation of polymer at the surface of the polymer base membrane. Formed through light -induced branches aggregation reactions.
It improves the adhesion between the polymer base film and the metal layer, and enhances the structural stability of the composite fluid, and improves its performance in battery applications.
Smart Images

Figure CN115939410B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a composite current collector and a preparation method thereof, an electrode and a secondary battery. Background Art
[0002] At present, composite current collectors based on polymer films have received widespread attention and application in the new energy industry. The preparation process of the composite current collector is usually: a layer of metal (aluminum, copper, etc.) material is deposited on a polymer film (such as polypropylene, polyethylene, polyester, etc.) by physical vapor deposition (PVD). The prepared surface metallized film with a certain conductivity is the composite current collector. Compared with traditional current collectors, composite current collectors based on polymer films have the characteristics of low cost, light weight, and good internal insulation. These characteristics enable the composite current collector to reduce the cost of the battery and improve the energy density and safety of the battery when used in the battery.
[0003] For composite current collectors, since the surface polarity of the polymer film used is usually weak, its surface tension is low and the surface adhesion performance is weak, which leads to the weak adhesion between the polymer base film and the metal layer in the prepared composite current collector, and finally leads to the poor structural stability of the composite current collector, which affects the normal use of the composite current collector. Therefore, in view of the above problems, it is necessary to develop a composite current collector with a stable structure, so as to improve the structural stability of the current composite current collector, so as to promote the promotion and application of the composite current collector. Summary of the invention
[0004] Based on this, the present application provides a composite current collector and a preparation method thereof, an electrode and a secondary battery, which can improve the adhesion between the polymer base film and the metal layer, thereby improving the structural stability of the composite current collector.
[0005] The first aspect of the present application provides a composite current collector, comprising a polymer base film and composite layers arranged on both sides of the polymer base film, each of the composite layers comprising:
[0006] A modified layer disposed on the polymer base film and a metal layer disposed on the surface of the modified layer, wherein the material of the modified layer comprises a polymer formed by in-situ polymerization of a polymer monomer on the surface of the polymer base film; the polymer monomer comprises at least one of an acrylamide monomer and a butenoic acid monomer;
[0007] The structure of the acrylamide monomer is shown in Formula I-1 or Formula I-2:
[0008]
[0009] In formula I-1 and formula I-2, R1 and R2 are each independently hydrogen, fluorine, chlorine or bromine, R3 is hydrogen, methyl, hydroxymethyl, ethyl, hydroxyethyl, fluorine, chlorine or bromine; R4 and R5 are each independently hydrogen, an alkyl group having 1 to 5 carbon atoms, a phenyl group or an acrylamide group; n represents an integer of 2 to 10;
[0010] The structure of the butenoic acid monomer is shown in Formula II-1 or II-2:
[0011]
[0012] In formula II-1 and formula II-2, R6 is hydrogen, hydroxyl, fluorine, chlorine or bromine; R7 and R8 are each independently hydrogen, methyl, hydroxymethyl, fluorine, chlorine or bromine; and m represents an integer of 2 to 10.
[0013] In some embodiments of the present application, the modified layer satisfies at least one of the following conditions:
[0014] (1) The polymer of the modified layer includes a homopolymer of the butenoic acid monomer;
[0015] Optionally, the polymer is selected from at least one of polybutenoic acid, poly(4-hydroxybutenoic acid), poly(2-hydroxymethylbutenoic acid), poly(2,3-dihydroxymethylbutenoic acid), poly(3-chlorobutenoic acid), poly(3-chloro-4-hydroxybutenoic acid), poly(3,4-dichlorobutenoic acid), poly(2,3-dichloro-4-hydroxybutenoic acid), poly(2,3,4-trichlorobutenoic acid), poly(4-bromobutenoic acid), and poly(4-fluorobutenoic acid);
[0016] (2) The polymer of the modified layer includes a homopolymer of the acrylamide monomer;
[0017] Optionally, the polymer is selected from at least one of polyacrylamide, polymethacrylamide, poly(N,N-methylenebisacrylamide), poly(N,N-dimethylacrylamide), poly(N-isopropylacrylamide), poly(N-tert-butylacrylamide), poly(N-phenylacrylamide), poly(2-chloro-acrylamide), poly(2-hydroxymethyl-acrylamide), poly(3-bromo-acrylamide), and poly(2-hydroxymethyl-3-bromo-acrylamide);
[0018] (3) The polymer of the modified layer includes a polyacrylamide-polyacrylamide copolymer formed by different acrylamide monomers;
[0019] (4) The polymer of the modified layer includes a polybutylene acid-polyacrylamide copolymer formed by the acrylamide monomer and the butylene acid monomer;
[0020] (5) The polymer of the modified layer includes a polybutylene copolymer formed from different butylene monomers.
[0021] In some embodiments of the present application, the composite current collector satisfies at least one of the following conditions:
[0022] (1) The thickness of the modified layer is 20 nm to 100 nm;
[0023] (2) The thickness of the polymer base film is 2 μm to 20 μm,
[0024] Optionally, the material of the polymer base film includes one or more of polypropylene, polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polypropylene, polyvinyl chloride, polyvinylidene fluoride and polystyrene;
[0025] (3) The thickness of the metal layer is 500nm to 2000nm,
[0026] Optionally, the material of the metal layer includes one or more of copper, copper alloy, aluminum, aluminum alloy, nickel, nickel alloy, titanium and silver.
[0027] In some embodiments of the present application, the composite layer further comprises a protective layer, and the protective layer is disposed on a surface of the metal layer that is relatively far from the modified layer.
[0028] Optionally, the thickness of the protective layer is 10 nm to 150 nm.
[0029] Optionally, the material of the protective layer includes one or more of nickel, chromium, nickel-based alloy, copper-based alloy, copper oxide, aluminum oxide, nickel oxide, chromium oxide, cobalt oxide, graphite, carbon black, acetylene black, Ketjen black, carbon nano-quantum dots, carbon nanotubes, carbon nanofibers and graphene.
[0030] The second aspect of the present application provides a method for preparing a composite current collector, comprising:
[0031] Performing a surface modification treatment of the polymer base film by photoinduced graft polymerization to form a modified layer; and
[0032] forming a metal layer on the surface of the modified layer;
[0033] The photoinduced graft polymerization surface modification treatment comprises: in the presence of a photosensitizer, allowing the polymerization monomer to undergo a photoinduced graft polymerization reaction to form a polymer; the polymerization monomer comprises at least one of an acrylamide monomer and a butenoic acid monomer;
[0034] The structure of the acrylamide monomer is shown in Formula I-1 or Formula I-2:
[0035]
[0036] In formula I-1 and formula I-2, R1 and R2 are each independently hydrogen, fluorine, chlorine or bromine, R3 is hydrogen, methyl, hydroxymethyl, ethyl, hydroxyethyl, fluorine, chlorine or bromine; R4 and R5 are each independently hydrogen, an alkyl group having 1 to 5 carbon atoms, a phenyl group or an acrylamide group; n represents an integer of 2 to 10;
[0037] The structure of the butenoic acid monomer is shown in Formula II-1 or II-2:
[0038]
[0039] In formula II-1 and formula II-2, R6 is hydrogen, hydroxyl, fluorine, chlorine or bromine; R7 and R8 are each independently hydrogen, methyl, hydroxymethyl, fluorine, chlorine or bromine; and m represents an integer of 2 to 10.
[0040] In some embodiments of the present application, the process of performing photoinduced graft polymerization surface modification treatment on the surface of the polymer base film includes:
[0041] The polymer base film is immersed in a solution containing a polymerization monomer and a photosensitizer for pretreatment;
[0042] In an inert atmosphere, the polymer base film immersed in the solution is irradiated with an ultraviolet lamp, so that a graft polymerization reaction occurs on the surface of the polymer base film under the induction of the ultraviolet light to form the modified layer.
[0043] In some embodiments of the present application, the preparation method satisfies at least one of the following conditions:
[0044] (1) In the solution, the concentration of the polymerizable monomer is 0.5 mol / L to 1.3 mol / L,
[0045] (2) In the solution, the concentration of the photosensitizer is 0.1 mol / L to 0.3 mol / L,
[0046] (3) The photosensitizer includes a benzophenone photosensitizer;
[0047] Optionally, the benzophenone photosensitizer includes one or more of benzophenone, 2,4-dihydroxybenzophenone and Michler's ketone.
[0048] In some embodiments of the present application, the preparation method satisfies at least one of the following conditions:
[0049] (1) The distance between the UV lamp and the polymer base film is 10 cm to 30 cm;
[0050] (2) The power density of the ultraviolet lamp is 50W / cm2 to 250W / cm2;
[0051] (3) The irradiation time of the ultraviolet lamp is 10s to 200s.
[0052] In some embodiments of the present application, the preparation method satisfies at least one of the following conditions:
[0053] (1) The polymerizable monomer is selected from one or more of the butenoic acid monomers;
[0054] (2) the polymerizable monomer is selected from one or more of the acrylamide monomers;
[0055] (3) The polymerizable monomers include the acrylamide monomers and the crotonic acid monomers.
[0056] In some embodiments of the present application, after forming the modified layer, the method further comprises:
[0057] The polymer base film including the modified layer is cleaned and dried.
[0058] Optionally, the cleaning temperature is 70°C to 90°C.
[0059] Optionally, the cleaning process takes 5 to 10 minutes.
[0060] Optionally, the drying temperature is 60°C to 80°C.
[0061] In some embodiments of the present application, the preparation method further comprises:
[0062] A protective layer is formed on a surface of the metal layer at a side relatively far from the modified layer.
[0063] The materials of the polymer base film, the metal layer and the protective layer are as described in the first aspect of the present application and will not be repeated here.
[0064] The third aspect of the present application provides a composite current collector prepared by the preparation method of the second aspect of the present application.
[0065] The fourth aspect of the present application provides an electrode, comprising the composite current collector of the first aspect of the present application or the composite current collector of the third aspect of the present application.
[0066] The fifth aspect of the present application provides a secondary battery, including the electrode of the fourth aspect of the present application. The composite current collector provided by the present application is provided with a modified layer between the polymer base film and the metal layer. The polar functional groups such as carbonyl, amine, carboxyl, fluorine, chlorine or bromine contained in the polymer contained in the modified layer can make the modified layer have a higher polarity, and easily interact with metal atoms, so that the modified layer and the metal layer have a higher bonding force. In addition, the modified layer can improve the bonding force with the polymer base film by chemically bonding with the polymer base film. Therefore, by setting the modified layer, the modified layer and the metal layer, and the modified layer and the polymer base film can have a higher bonding at the same time, thereby improving the structural stability of the composite current collector as a whole. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 Schematic diagram of the structure of a composite current collector according to one embodiment of the present application.
[0068] Figure 2 This is a schematic structural diagram of a composite current collector according to another embodiment of the present application.
[0069] Figure 3 This is a cross-sectional morphology diagram of the polypropylene film having a modified layer on its surface in Example 1 of the present application.
[0070] Figure 4 This is a cross-sectional morphology diagram of the polypropylene film having a modified layer on its surface after surface enhanced cleaning treatment in Example 1 of the present application. DETAILED DESCRIPTION
[0071] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0072] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0073] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art in the technical field of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. It should be noted that, unless otherwise specified, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above" and "below" include the number, and the meaning of "multiple" in "one or more" is more than two.
[0074] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0075] During the research process, the inventors found that in the current conventional composite current collectors, due to the weak surface polarity of the high molecular polymer base film used, it is easy to cause the base film to have low surface tension and weak surface adhesion performance, which will cause the adhesion between the base film and the metal layer of the prepared composite current collector to be weak, and ultimately lead to poor structural stability of the composite current collector.
[0076] In order to solve the above-mentioned technical problems, the inventors started from the perspective of surface modification of the polymer base film, and constructed a modified layer containing a functional functional group polymer between the base film and the metal layer, so that the modified layer and the base film are connected by covalent bonds, and the modified layer has a higher polarity, thereby promoting the adhesion with the metal layer and enhancing the structural stability of the composite current collector.
[0077] In a first aspect, the present application provides a composite current collector, such as Figure 1 As shown, it comprises: a polymer base film 1 and composite layers arranged on both sides of the polymer base film 1, each of the composite layers comprises: a modified layer 2 arranged on the surface of the polymer base film and a metal layer 3 arranged on the surface of the modified layer 2 relatively away from the polymer base film 1, wherein the material of the modified layer comprises a polymer formed by in-situ polymerization of a polymer monomer on the surface of the polymer base film; the polymer monomer comprises at least one of an acrylamide monomer and a butenoic acid monomer;
[0078] The structure of the acrylamide monomer is shown in Formula I-1 or Formula I-2:
[0079]
[0080] In formulas I-1 and I-2, R1 and R2 are each independently hydrogen, fluorine, chlorine or bromine, R3 is hydrogen, methyl, hydroxymethyl, ethyl, hydroxyethyl, fluorine, chlorine or bromine; R4 and R5 are each independently hydrogen, an alkyl group having 1 to 5 carbon atoms, a phenyl group or an acrylamide group; n represents an integer of 2 to 10;
[0081] The structure of the butenoic acid monomer is shown in Formula II-1 or II-2:
[0082]
[0083] In formulae II-1 and II-2, R6 is hydrogen, hydroxyl, fluorine, chlorine or bromine; R7 and R8 are each independently hydrogen, methyl, hydroxymethyl, fluorine, chlorine or bromine; and m represents an integer of 2 to 10.
[0084] The composite current collector provided in the present application has a modified layer between the polymer base film and the metal layer. The polar functional groups such as carbonyl, amine, carboxyl, fluorine, chlorine or bromine contained in the polymer contained in the modified layer can make the modified layer have a higher polarity, and it is easy to interact with metal atoms, so that the modified layer and the metal layer have a higher adhesion. In addition, the modified layer is chemically bonded to the polymer base film, and the reaction process (taking acrylamide monomers as an example) can be schematically represented by the following formula (1), and the adhesion with the polymer base film can be improved through chemical bonding. Therefore, by setting the modified layer, the modified layer and the metal layer, and the modified layer and the polymer base film can have a higher adhesion at the same time, thereby improving the structural stability of the composite current collector as a whole.
[0085]
[0086] In some embodiments, the modified layer includes a homopolymer of the butenoic acid monomer. Alternatively, the polybutenoic acid may include at least one of polybutenoic acid, poly(4-hydroxybutenoic acid), poly(2-hydroxymethylbutenoic acid), poly(2,3 dihydroxymethylbutenoic acid), poly(3-chlorobutenoic acid), poly(3-chloro-4-hydroxybutenoic acid), poly(3,4-dichlorobutenoic acid), poly(2,3-dichloro-4-hydroxybutenoic acid), poly(2,3,4-trichlorobutenoic acid), poly(4-bromobutenoic acid), and poly(4-fluorobutenoic acid).
[0087] In some embodiments, the polymer of the modified layer includes a homopolymer of the acrylamide monomer. Alternatively, the polyacrylamide may include at least one of polyacrylamide, polymethacrylamide, poly(N,N-methylenebisacrylamide), poly(N,N-dimethylacrylamide), poly(N-isopropylacrylamide), poly(N-tert-butylacrylamide), poly(N-phenylacrylamide), poly(2-chloro-acrylamide), poly(2-hydroxymethyl-acrylamide), poly(3-bromo-acrylamide), and poly(2-hydroxymethyl-3-bromo-acrylamide).
[0088] In some embodiments, the polymer of the modified layer includes a polyacrylamide-polyacrylamide copolymer formed by different acrylamide monomers. For example, the polymer of the modified layer can be formed by monomers of formula I-1 and formula I-1, or by monomers of formula II-2 and formula II-2.
[0089] In some embodiments, the polymer of the modified layer includes a polybutylene-acrylamide copolymer formed by the acrylamide monomer and the butylene monomer. For example, the polymer of the modified layer can be formed by monomers of formula I-2 and formula II-1, or by monomers of I-1 and formula II-2, etc., which will not be repeated here.
[0090] In some embodiments, the polymer of the modified layer includes a polybutylene copolymer formed from different butylene monomers. For example, the polymer of the modified layer can be formed from monomers of Formula II-1 and Formula II-2.
[0091] In some embodiments, the thickness of the modified layer can be 20nm to 100nm. For example, the thickness of the modified layer can be 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or within the range of any of the above values. The thickness of the modified layer is set considering that the role of the modified layer is to improve the surface structure and properties of the polymer base film. Increasing the thickness of the modified layer under the premise of uniform modification does not further improve the surface structure and properties, but will increase the cost of raw materials and may cause the problem of uneven modification, so the modified layer should not be too thick. The thickness of the modified layer is controlled within an appropriate range, which can not only make the modified layer have a better effect of improving adhesion, but also avoid the phenomenon of uneven modification.
[0092] In some embodiments, the thickness of the polymer base film is 2 μm to 20 μm. The thickness of the polymer base film is set in consideration of the application requirements of the composite current collector, while taking into account the difficulty and cost of the preparation process. Optionally, the polymer base film can be prepared by a melt-extrusion-biaxial stretching method.
[0093] In some embodiments, the material of the polymer-based film may include one or more of polypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polypropylene, polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyphenylene sulfide (PPS), polyphenylene oxide (PPO), polystyrene (PS), and polyimide (PI).
[0094] In some embodiments, the thickness of the metal layer may be 500 nm to 2000 nm, and optionally, the thickness of the metal layer may be 700 nm to 1200 nm. When the thickness of the metal layer is controlled within a suitable range, the composite current collector may have a higher conductivity.
[0095] It is understandable that the metal layer can be disposed on two opposite sides of the polymer base film at the same time; the thickness of the metal layers on the two sides can be the same or different, and the specific arrangement can be selected according to actual needs.
[0096] In some embodiments, the preparation method of the metal layer is not particularly limited and can be selected according to actual needs. For example, it can be prepared by physical vapor deposition (such as resistance heating vacuum evaporation, electron beam heating vacuum evaporation, laser heating vacuum evaporation or magnetron sputtering, etc.), electroplating, chemical plating, etc.
[0097] In some embodiments, the material of the metal layer is not particularly limited and can be selected according to actual needs. For example, the material of the metal layer can include one or more of copper, copper alloy, aluminum, aluminum alloy, nickel, nickel alloy, titanium and silver.
[0098] In some embodiments, the composite current collector may further include a protective layer disposed on a surface of the metal layer that is relatively far from the modified layer.
[0099] In some embodiments, the thickness of the protective layer may be 10 nm to 150 nm. The protective layer is mainly used to prevent the metal layer from being chemically corroded or physically damaged. The thickness of the protective layer is within a suitable range, which not only provides a good protective effect, but also does not affect the conductivity of the metal layer. Optionally, the thickness of the protective layer is 20 nm to 100 nm, which ensures a high conductivity while ensuring a protective effect.
[0100] The present application does not specifically limit the material of the protective layer, and the material can be selected according to actual needs. For example, the material of the protective layer may include one or more of nickel, chromium, nickel-based alloy, copper-based alloy, copper oxide, aluminum oxide, nickel oxide, chromium oxide, cobalt oxide, graphite, carbon black, acetylene black, Ketjen black, carbon nano quantum dots, carbon nanotubes, carbon nanofibers and graphene.
[0101] It can be understood that the protective layer can be set on one side of the polymer base film, or it can be set on both opposite sides of the polymer base film at the same time; when set at the same time, the thickness of the protective layers on both sides can be the same or different, and the specific setting method can be selected according to actual needs.
[0102] The second aspect of the present application provides a method for preparing a composite current collector, which may include the following steps:
[0103] S10, performing a surface modification treatment of the polymer base film by photoinduced graft polymerization to form a modified layer, wherein the surface modification treatment by photoinduced graft polymerization comprises: in the presence of a photosensitizer, allowing a polymerizable monomer to undergo a photoinduced graft polymerization reaction to form a polymer, wherein the polymerizable monomer comprises at least one of an acrylamide monomer and a butyric acid monomer;
[0104] The structure of the acrylamide monomer is shown in Formula I-1 or Formula I-2:
[0105]
[0106] In formulas I-1 and I-2, R1 and R2 are each independently hydrogen, fluorine, chlorine or bromine, R3 is hydrogen, methyl, hydroxymethyl, ethyl, hydroxyethyl, fluorine, chlorine or bromine; R4 and R5 are each independently hydrogen, an alkyl group having 1 to 5 carbon atoms, a phenyl group or an acrylamide group; n represents an integer of 2 to 10;
[0107] The structure of the butenoic acid monomer is shown in Formula II-1 or II-2:
[0108]
[0109]
[0110] In formula II-1 and II-2, R6 is hydrogen, hydroxy, fluorine, chlorine or bromine; R7 and R8 are each independently hydrogen, methyl, hydroxymethyl, fluorine, chlorine or bromine; m represents an integer of 2 to 10; and
[0111] S20, forming a metal layer on the surface of the modified layer.
[0112] The present application adopts a method of photoinduced graft polymerization to prepare a modified layer in situ on the surface of a polymer base film. The polymer contained in the prepared modified layer contains polar functional groups such as carbonyl, amine, carboxyl, fluorine, chlorine or bromine. These polar functional groups can make the modified layer have a higher polarity and easily interact with metal atoms, so that the modified layer and the metal layer have a higher bonding force. In addition, the modified layer can improve the bonding force with the polymer base film by chemically bonding with the polymer base film.
[0113] In some implementations, the above step S10 may specifically include the following steps:
[0114] S110, immersing the polymer base film in a solution containing a polymerization monomer and a photosensitizer for pretreatment;
[0115] S120, irradiating the polymer base film immersed in the solution with an ultraviolet lamp in an inert atmosphere, so that a graft polymerization reaction occurs on the surface of at least one side of the polymer base film under the induction of ultraviolet light, forming the modified layer, and obtaining a composite film layer.
[0116] In some embodiments, the polymerizable monomer may include an acrylamide monomer and / or a crotonic acid monomer.
[0117] It is understandable that the polymerized monomers in step S110 may be only acrylamide monomers, or only crotonic acid monomers, or both acrylamide monomers and crotonic acid monomers may exist.
[0118] In some embodiments, the acrylamide monomer may include one or more of acrylamide, methacrylamide, N,N′-methylenebisacrylamide, N,N-dimethylacrylamide, N-isopropylacrylamide, N-tert-butylacrylamide, N-phenylacrylamide, 2-chloro-acrylamide, 2-hydroxymethyl-acrylamide, 3-bromo-acrylamide, and 2-hydroxymethyl-3-bromo-acrylamide.
[0119] In some embodiments, the butenoic acid monomers may include one or more of butenoic acid, 4-hydroxybutenoic acid, 2-hydroxymethylbutenoic acid, 2,3-dihydroxymethylbutenoic acid, 3-chlorobutenoic acid, 3-chloro-4-hydroxybutenoic acid, 3,4-dichlorobutenoic acid, 2,3-dichloro-4-hydroxybutenoic acid, 2,3,4-trichlorobutenoic acid, 4-bromobutenoic acid, and 4-fluorobutenoic acid.
[0120] The acrylamide monomers and butenoic acid monomers provided in the present application are reactive and can be polymerized in situ on the surface of the polymer base film under the action of ultraviolet light induction. Specifically, the C=C double bonds in the acrylamide monomers and butenoic acid monomers can undergo addition reactions with the opened CH bonds in the methyl groups of the polymer base film macromolecules to form a seed layer of the modified layer and form a chemical bond with the polymer base film, thereby achieving a connection between the modified layer and the polymer base film through a chemical bond, improving the bonding force with the polymer base film, and further improving the polymerization stability of the composite current collector.
[0121] At the same time, based on the above-mentioned seed layer, the residual CH bonds in the surface molecules of the seed layer can be broken under the induction of ultraviolet light, and further react with the C=C double bonds in the new reactive monomers acrylamide and butenoic acid molecules, and so on, to achieve in-situ polymerization of acrylamide and acrylic acid reactive monomers on the membrane surface to form a corresponding modified layer.
[0122] In some embodiments, in the solution containing the polymerizable monomer and the photosensitizer, the concentration of the polymerizable monomer is 0.5 mol / L to 1.3 mol / L. For example, the concentration of the polymerizable monomer may be 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L or within the range of any of the above values. In this embodiment, the uniformity of the formed modified layer can be further improved while ensuring the grafting effect.
[0123] If the concentration of the polymerized monomer is relatively low, the modification effect may not be obvious; if the concentration of the polymerized monomer is relatively high, the reaction may be more violent, which may easily lead to changes in the uniformity of the modified layer.
[0124] In some embodiments, in the solution containing the polymerizable monomer and the photosensitizer, the concentration of the photosensitizer may be 0.1 mol / L to 0.3 mol / L. For example, the concentration of the photosensitizer may be 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, or within the range of any of the above values. If the concentration of the photosensitizer is low, the modification effect is not obvious; if the concentration of the photosensitizer is high, the reaction is too violent, which may lead to poor uniformity of the modified layer.
[0125] In some embodiments, the photosensitizer may include a benzophenone photosensitizer. For example, the benzophenone photosensitizer may include one or more of benzophenone, 2,4-dihydroxybenzophenone, Michler's ketone, and derivatives of the above photosensitizers. The photosensitizer may absorb ultraviolet light, generate free radicals, and induce a reaction of a reactive monomer.
[0126] In some embodiments, the solvent contained in the solution containing the polymerizable monomer and the photosensitizer may be a ketone solvent, for example, the solvent may include, but is not limited to, one or more of acetone, butanone, and pentanone.
[0127] It should be noted that the above-mentioned photoinduced graft polymerization reaction can be carried out in a photoinduced graft polymerization device, which may include a gas supply unit, a pre-treatment unit, a reaction unit, a cleaning unit, and the like.
[0128] In some embodiments, the gas supply unit may input nitrogen into the reaction device to provide an inert gas protective atmosphere to protect the generation of free radical intermediates during the reaction process.
[0129] In some embodiments, the reaction unit is mainly composed of two rows of ultraviolet lamps, and the distance between the ultraviolet lamps and the polymer base film can be 10 cm to 30 cm. If the distance is too high or too low, the intensity of ultraviolet light radiated to the film surface may be affected, resulting in poor treatment effect.
[0130] In some embodiments, the UV lamp may be a high-pressure UV lamp, and the power density of the UV lamp may be 50W / cm2 to 250W / cm2. If the power density is too low, the reaction efficiency may be low, resulting in poor modification effect; if the power density is too high, the reaction may be too fast, resulting in uneven reaction.
[0131] In some embodiments, the irradiation time of the ultraviolet lamp can be 10s to 200s. If the time is too short, the modification effect is not good; if the time is too long, the modification is not uniform, resulting in poor effect.
[0132] In some embodiments, after obtaining the composite film layer, the following steps may also be included:
[0133] S130, cleaning and drying the composite film layer.
[0134] In the above step S130, the composite film layer may be passed into a cleaning unit. Optionally, the cleaning unit may be a hot water cleaning tank.
[0135] In some embodiments, the cleaning process may be performed at a temperature of 70°C to 90°C.
[0136] In some embodiments, the cleaning process may last for 5 to 10 minutes.
[0137] In the above step S130, the cleaned composite film layer may be placed in an oven for drying.
[0138] In some embodiments, the drying process may be performed at a temperature of 60°C to 80°C.
[0139] In some embodiments, the preparation method may further include the following steps:
[0140] S30, forming a protective layer on a surface of the metal layer that is relatively far away from the modified layer.
[0141] In some embodiments, the preparation method of the protective layer is not particularly limited and can be selected according to actual needs. For example, it can include one or more methods such as physical vapor deposition, chemical vapor deposition, in-situ forming, and coating. Among them, the vapor deposition method is preferably vacuum evaporation and magnetron sputtering; the chemical vapor deposition is preferably atmospheric pressure chemical vapor deposition and plasma enhanced chemical vapor deposition; the in-situ forming is preferably a method of forming a metal oxide passivation layer in situ on the surface of the metal layer; the coating method is preferably die coating, blade coating, and extrusion coating.
[0142] The third aspect of the present application provides an electrode, comprising the composite current collector of the first aspect of the present application or the composite current collector prepared by the method of the second aspect of the present application.
[0143] In some embodiments, the electrode includes a positive electrode and / or a negative electrode.
[0144] A fourth aspect of the present application provides a secondary battery, comprising the electrode according to the third aspect of the present application.
[0145] In some embodiments, the secondary battery may include a lithium ion secondary battery or a sodium ion secondary battery.
[0146] In some embodiments, the secondary battery includes a positive electrode, a negative electrode, an electrolyte and a separator. During the battery charge and discharge process, active ions are inserted and removed back and forth between the positive electrode and the negative electrode. The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The separator is arranged between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0147] The fifth aspect of the present application provides an electrical device, including the secondary battery of the fourth aspect of the present application. The secondary battery can be used as a power source for the device, and can also be used as an energy storage unit for the device. The device can be, but is not limited to, a mobile device, an electric vehicle, an electric train, a ship and a satellite, an energy storage system, etc. For example, it can be a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini CD, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, etc.
[0148] Example
[0149] The following are specific examples, which more specifically describe the contents disclosed in this application, and these examples are only for illustrative purposes, because it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0150] Example 1
[0151] Preparation of composite current collector
[0152] Preparation of modified layer: First, prepare an acetone solution of 0.5 mol / L acrylamide and 0.1 mol / L benzophenone and pour it into the tank of the pretreatment unit. Then, place a commercial biaxially oriented polypropylene base film (manufacturer: Toray, Japan, thickness: 4.5 μm) in a photoinduced graft polymerization device, open the air inlet valve of the air inlet unit, and introduce nitrogen into the device. After the device is filled with nitrogen, place the polypropylene base film in the solution in the tank of the pretreatment unit and dip-coat for 30 seconds. After completion, turn on the ultraviolet lamp in the reaction unit, and the base film enters the reaction unit. The distance between the base film and the ultraviolet lamp is 10 cm, and the power density of the ultraviolet lamp is 50 W / cm, and the treatment is 10 seconds. After the treatment is completed, the film enters the cleaning unit from the reaction unit and is cleaned in 80°C pure water for 5 minutes. After cleaning, the film enters a 70°C oven and is dried to obtain a polypropylene film with a modified layer on the surface. Field emission electron microscopy (FESEM) was used to characterize the cross-sectional morphology of the modified polypropylene membrane and the modified polypropylene membrane after surface enhanced cleaning treatment, which indirectly proved that polyacrylamide was grafted on the surface of the polypropylene membrane. The conditions for surface enhanced cleaning treatment were: stirring and soaking in 80°C hot water for 48 hours; since polyacrylamide can be dissolved in hot water, if polyacrylamide is not grafted to the surface of the polypropylene membrane, the modified layer on the membrane surface will dissolve after surface enhanced cleaning treatment. Specific results Figure 3 and Figure 4 As shown, it can be seen that the modified layer still exists after the surface enhanced cleaning treatment, and the thickness has basically not changed, which proves that the modified layer is grafted to the polypropylene membrane surface.
[0153] Preparation of the metal layer: The polypropylene film with a modified layer on the surface prepared above is placed in a vacuum evaporation chamber, and the high-purity copper wire (purity greater than 99.99%) in the metal evaporation chamber is melted and evaporated at a high temperature of 1500°C. The evaporated metal atoms pass through the cooling system in the vacuum coating chamber and are deposited on the two surfaces of the polymer base film to form a copper metal conductive layer with a thickness of 1 micron.
[0154] Preparation of protective layer: 1g of graphene is evenly dispersed in 999g of nitrogen methyl pyrrolidone (NMP) solution by ultrasonic dispersion to prepare a coating liquid with a solid content of 0.1wt.%, and then the coating liquid is evenly coated on the surface of the metal conductive layer by a die coating process, where the coating amount is controlled at 80 microns, and finally dried at 75°C.
[0155] Example 2
[0156] The composite current collector was prepared according to the method of Example 1, except that during the preparation of the modified layer, the concentration of acrylamide in the solution was adjusted to 0.9 mol / L.
[0157] Example 3
[0158] The composite current collector was prepared according to the method of Example 1, except that during the preparation of the modified layer, the concentration of acrylamide in the solution was set to 1.3 mol / L.
[0159] Example 4
[0160] The composite current collector was prepared according to the method of Example 2, except that during the preparation of the modified layer, the concentration of benzophenone in the solution was adjusted to 0.2 mol / L.
[0161] Example 5
[0162] The composite current collector was prepared according to the method of Example 2, except that during the preparation of the modified layer, the concentration of benzophenone in the solution was adjusted to 0.3 mol / L.
[0163] Example 6
[0164] The composite current collector was prepared according to the method of Example 4, except that during the preparation of the modified layer, the distance between the base film and the ultraviolet lamp was adjusted to 20 cm.
[0165] Example 7
[0166] The composite current collector was prepared according to the method of Example 4, except that during the preparation of the modified layer, the distance between the base film and the ultraviolet lamp was adjusted to 30 cm.
[0167] Example 8
[0168] The composite current collector was prepared according to the method of Example 6, except that during the preparation of the modified layer, the power density of the UV lamp was adjusted to 150 W / cm.
[0169] Example 9
[0170] The composite current collector was prepared according to the method of Example 6, except that during the preparation of the modified layer, the power density of the UV lamp was adjusted to 250 W / cm.
[0171] Example 10
[0172] The composite current collector was prepared according to the method of Example 8, except that during the preparation of the modified layer, the reaction treatment time was adjusted to 100 s.
[0173] Embodiment 11
[0174] The composite current collector was prepared according to the method of Example 8, except that during the preparation of the modified layer, the reaction treatment time was adjusted to 200 s.
[0175] Example 12
[0176] A composite current collector was prepared according to the method of Example 10, except that in the process of preparing the modified layer, benzophenone was replaced by 2,4-dihydroxybenzophenone.
[0177] Example 13
[0178] The composite current collector was prepared according to the method of Example 10, except that acrylamide was replaced by N,N'-methylenebisacrylamide during the preparation of the modified layer.
[0179] Embodiment 14
[0180] The composite current collector was prepared according to the method of Example 10, except that acrylamide was replaced by crotonic acid during the preparation of the modified layer.
[0181] Embodiment 15
[0182] The composite current collector was prepared according to the method of Example 10, except that acrylamide was replaced by 4-hydroxybutenoic acid during the preparation of the modified layer.
[0183] Example 16
[0184] The composite current collector was prepared according to the method of Example 10, except that in the process of preparing the modified layer, acrylamide was replaced by a mixed monomer of acrylamide and 4-hydroxybutenoic acid.
[0185] Comparative Example 1
[0186] The composite current collector was prepared according to the method of Example 1, except that in the process of preparing the modified layer, the polypropylene film was not surface modified.
[0187] Comparative Example 2
[0188] The method is basically the same as Example 1, except that in the preparation process of the modified layer, only the acrylamide solution in the tank of the pretreatment unit is dip-coated, and no subsequent ultraviolet light irradiation treatment is performed.
[0189] Comparative Example 3
[0190] It is basically the same as Example 1, except that: during the preparation of the modified layer, the solution in the tank of the pretreatment unit is replaced with a polyacrylamide solution, and subsequent ultraviolet irradiation treatment and cleaning treatment are not performed.
[0191] Comparative Example 4
[0192] It is basically the same as Example 10, except that: the conventional treatment method, i.e., the corona method, is used instead of the in-situ photoinduced graft polymerization surface modification treatment provided in the present application, specifically: the polypropylene film is placed in a roll-to-roll corona treatment device, the corona power is selected to be 10 kW, the current is selected to be 6 A, and the surface of the polypropylene film is treated at a line speed of 100 m / min.
[0193] The composite current collectors prepared in Examples 1 to 16 and Comparative Examples 1 to 3 were subjected to relevant performance tests, wherein the adhesion between the base film and the metal layer of the composite current collector is a key indicator reflecting the structural stability of the composite current collector, and thus the adhesion between the base film and the metal layer was tested. The improvement in adhesion depends on the surface tension of the surface modification layer of the base film. Here, the surface tension of the modified polypropylene film was tested, and the storage stability of the modified polypropylene film was verified, that is, the change in surface tension after 3 months of storage, and then compared with the traditional corona treatment (corona treatment has the problem of storage instability). In addition, the thickness of the modified layer was characterized to verify the formation of the surface modification layer of the base film and analyze the influence of process conditions on the thickness of the modified layer. The test results are shown in Table 1 below, wherein " / " indicates that the performance does not exist.
[0194] Among them, the test conditions or test standards for each performance test item are as follows:
[0195] (1) Adhesion: A layer of Permacel P-94 double-sided tape was bonded to a 1 mm thick aluminum foil, the composite current collector sample was bonded on top of the double-sided tape, and a layer of ethylene acrylic acid copolymer film (DuPont Nurcel0903, 50 μm thick) was covered on top of the sample. Then, the adhesive strength was tested at 1.3 × 105 N / m 2 , hot press at 120℃ for 10s, cool to room temperature, and cut into 150mm×15mm strips. Finally, the ethylene acrylic acid copolymer film of the sample strip is fixed to the upper fixture of the tensile machine, and the rest is fixed to the lower fixture. After fixing, the two are peeled at an angle of 180° and a speed of 100mm / min to test the peeling force, that is, the bonding force between the base film and the metal layer in the composite current collector.
[0196] (2) The surface tension of the initial surface-modified base film and the surface-modified base film after storage for three months were tested in accordance with GB / T 14216-2008.
[0197] (3) Modified layer thickness: First, the surface-modified sample was placed in an argon ion polisher (Fischione 1061) using an argon ion beam. The sample is cut, and after cutting, the sample is sprayed with gold to prepare a cross-section sample; the prepared cross-section sample is then placed in a field emission electron microscope (Zeiss Gemini Sigma 300VP SEM), magnified 50,000 times, and after adjusting the clarity, the cross-section morphology of the sample is observed and a photo is output; finally, the thickness of the modified layer in the cross-section morphology photo is marked using the measurement software that comes with the electron microscope, thereby obtaining the thickness data of the modified layer.
[0198] Table 1
[0199]
[0200]
[0201] By comparing Examples 1 to 16 and Comparative Examples 1 to 3, it can be seen that: compared with the unmodified base film, the surface modification of the base film using the method provided in the present application can significantly improve the adhesion between the base film and the metal layer of the prepared composite current collector.
[0202] By comparing Example 1 and Comparative Example 2, it can be seen that the surface tension of the modified polypropylene base film prepared by directly dipping the polypropylene base film in the acrylamide solution in the pretreatment unit tank body without ultraviolet irradiation treatment is low, which is equal to the surface tension of the unmodified polypropylene film in Comparative Example 1. This is because only the acrylamide solution in the pretreatment unit tank body is dipped without ultraviolet irradiation treatment, resulting in acrylamide cannot be grafted to the surface of the polypropylene base film and cannot undergo self-polymerization reaction. The acrylamide monomer coated on the surface of the polypropylene film is washed away in the cleaning unit, and a modified layer cannot be formed on the surface of the polypropylene film. In Example 1, ultraviolet irradiation treatment is performed, so a modified layer is formed on the surface of the polypropylene film, and the modified layer effectively improves the stability of the surface tension of the polymer base film.
[0203] By comparing Example 1 and Comparative Example 3, it can be seen that: the polypropylene base film is directly dipped in the polyacrylamide solution in the pretreatment unit tank body, and no ultraviolet light irradiation treatment is performed. Although the surface tension of the prepared modified polypropylene base film is improved, the polyacrylamide modified layer does not undergo a grafting reaction with the polypropylene film, resulting in a low bonding force between the two, which ultimately leads to a low bonding force between the polymer base film and the metal layer of the prepared composite current collector, that is, the modified layer does not play the role of enhancing the bonding force between the polymer base film and the metal layer. The polyacrylamide modified layer in Example 1 undergoes a grafting reaction with the polypropylene film, which improves the bonding force between the two, and ultimately improves the bonding force between the polymer base film and the metal layer in the composite current collector.
[0204] By comparing Example 1 and Comparative Example 4, it can be seen that: compared with the traditional corona modification treatment, the surface tension of the modified polymer base film prepared by the method provided in this application is stable (the surface tension of the surface-modified polymer base film remains basically unchanged after being placed for three months), that is, the modified polymer base film can be placed for a period of time before preparing the composite current collector, which is not available in the traditional corona method; in addition, the adhesion between the base film and the metal layer of the composite current collector prepared by the method provided in this application is better, that is, the structure of the composite current collector is more stable. Finally, it should be noted that the adhesion between the base film and the metal layer mainly depends on the surface properties and structure of the modified layer. Under the premise that the modified layer is uniform, the adhesion has nothing to do with the thickness of the modified layer, and mainly depends on the surface properties, that is, the size of the surface tension.
[0205] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0206] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A composite current collector, characterized in that: It comprises a polymer base film and composite layers arranged on both sides of the polymer base film, each of the composite layers comprises: a modified layer arranged on the surface of the polymer base film and a metal layer arranged on the surface of the modified layer, wherein the material of the modified layer comprises a polymer formed by in-situ polymerization of a polymer monomer on the surface of the polymer base film, and the polymer monomer comprises at least one of an acrylamide monomer and a butenoic acid monomer; The structure of the acrylamide monomer is shown in Formula I-1: In formula I-1, R1 and R2 are each independently hydrogen, fluorine, chlorine or bromine; R3 is hydrogen, methyl, hydroxymethyl, ethyl, hydroxyethyl, fluorine, chlorine or bromine; R4 and R5 are each independently hydrogen, an alkyl group having 1 to 5 carbon atoms, a phenyl group or an acrylamide group; The structure of the butenoic acid monomer is shown in Formula II-1: In formula II-1, R6 is hydrogen, hydroxyl, fluorine, chlorine or bromine; R7 and R8 are each independently hydrogen, methyl, hydroxymethyl, fluorine, chlorine or bromine; The preparation process of the modified layer is as follows: performing a surface modification treatment of the polymer base film by photoinduced graft polymerization to form a modified layer; The photoinduced graft polymerization surface modification treatment comprises: in the presence of a photosensitizer, allowing the polymerization monomer to undergo a photoinduced graft polymerization reaction to form a polymer.
2. The composite current collector according to claim 1, characterized in that: The modified layer satisfies at least one of the following conditions: (1) The polymer of the modified layer includes a homopolymer of the butenoic acid monomer; (2) The polymer of the modified layer includes a homopolymer of the acrylamide monomer; (3) The polymer of the modified layer includes a polyacrylamide-polyacrylamide copolymer formed by different acrylamide monomers; (4) The polymer of the modified layer includes a polybutylene acid-polyacrylamide copolymer formed by the acrylamide monomer and the butylene acid monomer; (5) The polymer of the modified layer includes a polybutylene copolymer formed from different butylene monomers.
3. The composite current collector according to claim 2, characterized in that: The polymer of the modified layer is selected from at least one of polybutenoic acid, poly(4-hydroxybutenoic acid), poly(2-hydroxymethylbutenoic acid), poly(2,3-dihydroxymethylbutenoic acid), poly(3-chlorobutenoic acid), poly(3-chloro-4-hydroxybutenoic acid), poly(3,4-dichlorobutenoic acid), poly(2,3-dichloro-4-hydroxybutenoic acid), poly(2,3,4-trichlorobutenoic acid), poly(4-bromobutenoic acid), and poly(4-fluorobutenoic acid).
4. The composite current collector according to claim 2, characterized in that: The polymer is selected from at least one of polyacrylamide, polymethacrylamide, poly(N,N-methylenebisacrylamide), poly(N,N-dimethylacrylamide), poly(N-isopropylacrylamide), poly(N-tert-butylacrylamide) and poly(N-phenylacrylamide), poly(2-chloro-acrylamide), poly(2-hydroxymethyl-acrylamide), poly(3-bromo-acrylamide) and poly(2-hydroxymethyl-3-bromo-acrylamide).
5. The composite current collector according to claim 1 or 2, characterized in that: The composite current collector satisfies at least one of the following conditions: (1) The thickness of the modified layer is 20 nm to 100 nm; (2) The thickness of the polymer base film is 2 μm to 20 μm, (3) The thickness of the metal layer is 500nm to 2000nm.
6. The composite current collector according to claim 5, characterized in that: The material of the polymer base film includes one or more of polypropylene, polyethylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polypropylene, polyvinyl chloride, polyvinylidene fluoride and polystyrene.
7. The composite current collector according to claim 5, characterized in that: The material of the metal layer includes one or more of copper, copper alloy, aluminum, aluminum alloy, nickel, nickel alloy, titanium and silver.
8. The composite current collector according to claim 1 or 2, characterized in that: The composite layer further includes a protective layer, which is disposed on a surface of the metal layer at a side relatively far from the modified layer.
9. The composite current collector according to claim 8, characterized in that: The thickness of the protective layer is 10nm-150nm.
10. The composite current collector according to claim 8, characterized in that: The material of the protective layer includes one or more of nickel, chromium, nickel-based alloy, copper-based alloy, copper oxide, aluminum oxide, nickel oxide, chromium oxide, cobalt oxide, graphite, carbon black, acetylene black, Ketjen black, carbon nano-quantum dots, carbon nanotubes, carbon nanofibers and graphene.
11. A method for preparing a composite current collector, characterized in that: include: Performing a surface modification treatment of the polymer base film by photoinduced graft polymerization to form a modified layer; and forming a metal layer on the surface of the modified layer; The photoinduced graft polymerization surface modification treatment comprises: in the presence of a photosensitizer, allowing the polymerization monomer to undergo a photoinduced graft polymerization reaction to form a polymer; The polymerizable monomer includes at least one of an acrylamide monomer and a butene acid monomer; The structure of the acrylamide monomer is shown in Formula I-1: In formula I-1, R1 and R2 are each independently hydrogen, fluorine, chlorine or bromine; R3 is hydrogen, methyl, hydroxymethyl, ethyl, hydroxyethyl, fluorine, chlorine or bromine; R4 and R5 are each independently hydrogen, an alkyl group having 1 to 5 carbon atoms, a phenyl group or an acrylamide group; The structure of the butenoic acid monomer is shown in Formula II-1: In formula II-1, R6 is hydrogen, hydroxy, fluorine, chlorine or bromine; R7 and R8 are each independently hydrogen, methyl, hydroxymethyl, fluorine, chlorine or bromine.
12. The preparation method according to claim 11, characterized in that: The surface modification treatment of the polymer base film by photoinduced graft polymerization comprises the following steps: The polymer base film is immersed in a solution containing a polymerization monomer and a photosensitizer for pretreatment; In an inert atmosphere, the polymer base film immersed in the solution is irradiated with an ultraviolet lamp, so that a graft polymerization reaction occurs on the surface of the polymer base film under the induction of the ultraviolet light to form the modified layer.
13. The preparation method according to claim 12, characterized in that: The preparation method satisfies at least one of the following conditions: (1) In the solution, the concentration of the polymerizable monomer is 0.5 mol / L to 1.3 mol / L; (2) In the solution, the concentration of the photosensitizer is 0.1 mol / L to 0.3 mol / L; (3) The photosensitizer includes a benzophenone photosensitizer.
14. The preparation method according to claim 13, characterized in that: The benzophenone photosensitizer includes one or more of benzophenone, 2,4-dihydroxybenzophenone and Michler's ketone.
15. The preparation method according to claim 12, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The distance between the UV lamp and the polymer base film is 10 cm to 30 cm; (2) The power density of the ultraviolet lamp is 50W / cm2 to 250W / cm2; (3) The irradiation time of the ultraviolet lamp is 10s to 200s.
16. The preparation method according to any one of claims 11 to 15, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The acrylamide monomers include one or more of acrylamide, methacrylamide, N,N′-methylenebisacrylamide, N,N-dimethylacrylamide, N-isopropylacrylamide, N-tert-butylacrylamide, N-phenylacrylamide, 2-chloro-acrylamide, 2-hydroxymethyl-acrylamide, 3-bromo-acrylamide, and 2-hydroxymethyl-3-bromo-acrylamide; (2) The butenoic acid monomers include one or more of butenoic acid, 4-hydroxybutenoic acid, 2-hydroxymethylbutenoic acid, 2,3-dihydroxymethylbutenoic acid, 3-chlorobutenoic acid, 3-chloro-4-hydroxybutenoic acid, 3,4-dichlorobutenoic acid, 2,3-dichloro-4-hydroxybutenoic acid, 2,3,4-trichlorobutenoic acid, 4-bromobutenoic acid, and 4-fluorobutenoic acid.
17. The preparation method according to any one of claims 11 to 15, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The polymerizable monomer is selected from one or more of the butenoic acid monomers; (2) the polymerizable monomer is selected from one or more of the acrylamide monomers; (3) The polymerizable monomers include the acrylamide monomers and the crotonic acid monomers.
18. The preparation method according to any one of claims 11 to 15, characterized in that: After forming the modified layer, the method further includes: cleaning and drying the polymer base film including the modified layer.
19. The preparation method according to claim 18, characterized in that: The cleaning temperature is 70°C to 90°C.
20. The preparation method according to claim 18, characterized in that: The cleaning time is 5 to 10 minutes.
21. The preparation method according to claim 18, characterized in that: The temperature of the drying process is 60°C to 80°C.
22. The preparation method according to any one of claims 11 to 15, characterized in that: Also includes: A protective layer is formed on a surface of the metal layer at a side relatively far from the modified layer.
23. The preparation method according to claim 22, characterized in that: The material of the metal layer includes one or more of copper, copper alloy, aluminum, aluminum alloy, nickel, nickel alloy, titanium and silver.
24. The preparation method according to claim 22, characterized in that: The material of the protective layer includes one or more of nickel, chromium, nickel-based alloy, copper-based alloy, copper oxide, aluminum oxide, nickel oxide, chromium oxide, cobalt oxide, graphite, carbon black, acetylene black, Ketjen black, carbon nano-quantum dots, carbon nanotubes, carbon nanofibers and graphene.
25. A composite current collector prepared by the preparation method according to any one of claims 11 to 24.
26. An electrode, characterized in that The composite current collector comprises the composite current collector according to any one of claims 1 to 10 or the composite current collector according to claim 25.
27. A secondary battery, characterized in that: Comprising the electrode as claimed in claim 26.
Citation Information
Patent Citations
Current collector and preparation method and application thereof
CN110993958A
Multifunctional composite current collector and preparation method thereof
CN113707886A
Lithium battery diaphragm and preparation method thereof
CN115411454A
Composite negative electrode current collector and preparation method thereof
CN115458749A